HOPE AND INEVITABILITY IN 13 REASONS WHY. A COMPARATIVE DISCOURSE ANALYSIS OF THE SERIES’ FIRST SEASON AND IT’S BEYOND THE REASONS DOCUMENTARY COUNTERPART - Dr. Roberto GELADO-MARCOS,Santana Lois POCH-BUTLER,Dr. Plácido MORENO FELICES (Fonseca, Journal of Communication, 2023)
The release of 13 Reasons Why in March 2017 attracted not only audiences worldwide, but also a considerable amount of academic attention. A good share of the academic production on the series, though, has focused mostly on its effects. For this reason, and in an attempt to approach the debate from complementary angles, this paper aims at examining the motivations expressed by those involved in the creative process of the show and comparing them with the actual discourse in the series’ first season